Polymorphism of CLPG gene in three sheep breeds grown in the steppe zone of the Russian Federation - Gorlov, Ivan Fiodorovich; Shirokova, Nadezhda Vasilievna; Kolosov, Yuri Anatolievich; Kolosov, Anatoli Yurievich; Getmantseva, Lyubov Vladimirovna; Slozhenkina, Marina Ivanovna; Mosolova, Natalia Ivanovna; Anisimova, Elena Yurievna; Ponomariov, Viktor Vladimirovich (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study aims to investigate the callipyge gene (CLPG) polymorphism in sheep of Edilbay, Volgograd, and Kalmyk breeds. Materials and Methods: The analysis was performed by the polymerase chain reaction–restriction fragment length polymorphisms method. The objects of the study were Edilbay fat-tailed sheep (n = 500) at the breeding plant Volgograd-Edilbay (Volgograd region), Volgograd finewool sheep (n = 500) at the breeding plant Romashkovskiy (Volgograd region), and Kalmyk fattailed sheep (n = 500) at the breeding plant Kirovsky (the Republic of Kalmykia, Yashkul rayon). To conduct the research, tissue samples of 1 cm² from sheep of Kalmyk and Edilbay breeds were taken from the auricle. Results: The allelic CLPG gene variants have been determined and genotypes of representative sampling of the three breeds of livestock grown in the steppe zone of Russia. The presented results of the CLPG gene polymorphism in these sheep breeds grown in Russia were obtained for the first time. The research study has revealed that in terms of the CLPG gene, the Edilbay, Volgograd, and Kalmyk sheep breeds have only a homozygous form. Conclusion: The results obtained expand the current understanding of the molecular markers that characterize the meat qualities of sheep. J. Adv. Vet. Anim. Res., 7(1): 51-55, March 2020